Testosterone therapy delays cardiomyocyte aging via an androgen receptor-independent pathway - L. Zhang (Brazilian Journal of Medical and Biological Research, 2011)
The testicular feminized (Tfm) mouse carries a nonfunctional androgen receptor (AR) and reduced circulating testosterone levels. We used Tfm and castrated mice to determine whether testosterone modulates markers of aging in cardiomyocytes via its classic AR-dependent pathway or conversion to estradiol. Male littermates and Tfm mice were divided into 6 experimental groups. Castrated littermates (group 1) and sham-operated Tfm mice (group 2, N = 8 each) received testosterone. Sham-operated Tfm mice received testosterone in combination with the aromatase inhibitor anastrazole (group 3, N = 7). Castrated littermates (group 4) and sham-operated untreated Tfm mice (group 5) were used as controls (N = 8 and 7, respectively). An additional control group (group 6) consisted of age-matched non-castrated littermates (N = 8). Cardiomyocytes were isolated from the left ventricle, telomere length was measured by quantitative PCR and expression of p16INK4α, retinoblastoma (Rb) and p53 proteins was detected by Western blot 3 months after treatment. Compared with group 6, telomere length was short (P < 0.01) and expression of p16INK4α, Rb and p53 proteins was significantly (P < 0.05) up-regulated in groups 4 and 5. These changes were improved to nearly normal levels in groups 1 and 2 (telomere length = 0.78 ± 0.05 and 0.80 ± 0.08; p16INK4α = 0.13 ± 0.03 and 0.15 ± 0.04; Rb = 0.45 ± 0.05 and 0.39 ± 0.06; p53 = 0.16 ± 0.04 and 0.13 ± 0.03), but did not differ between these two groups. These improvements were partly inhibited in group 3 compared with group 2 (telomere length = 0.65 ± 0.08 vs 0.80 ± 0.08, P = 0.021; p16INK4α = 0.28 ± 0.05 vs 0.15 ± 0.04, P = 0.047; Rb = 0.60 ± 0.06 vs 0.39 ± 0.06, P < 0.01; p53 = 0.34 ± 0.06 vs 0.13 ± 0.03, P = 0.004). In conclusion, testosterone deficiency contributes to cardiomyocyte aging. Physiological testosterone can delay cardiomyocyte aging via an AR-independent pathway and in part by conversion to estradiol.